READING: THE DEVELOPMENT OF LITERARY CONCEPTS - Henry, George H. (McGill Journal of Education / Revue des sciences de l’éducation de McGill, 1979)
Terms such as plot, character, and setting are familiar to everyone who has been through the slow mill of high school English. Yet they are remembered by most (including many who have become teachers in their turn) as a wooden coinage, a set of rather clumsy labels which seem intended to be hung round the necks of imaginary bottles (as in a lab) containing variously coloured but insipid extracts that once were part of a living story. George Henry is at pains to tease out a process, based on the modern understanding of reality, by which students should be led gradually to develop these concepts as in themselves living elements and essential to the life of any literary work of art: a process that he envisages as spanning ail the years of education and never ceasing in development.